Development and Evaluation of the “Pico Party Adventure” Game to Measure Learning Experience for Special Needs Students - Ramli, Halina; Md Ibharim, Laili Farhana; Bulut, Mehmet Akın; Yurdunkulu, Adem (Journal of ICT in Education, 2025)
The present study aims to elucidate the development process of an interactive educational game titled “Pico Party Adventure,” designed for special needs students, particularly those with learning difficulties. Furthermore, it reports on the levels of learning experience, referencing Kolb’s experiential learning criteria concerning engagement, competence, emotional, and social aspects. The 2D adventure-based game was developed using Scratch, following the ADDIE model. A survey using questionnaires was employed to evaluate user experience among 30 seven-year-old students with learning difficulties. The findings indicate that user experience levels were high regarding engagement and competence, moderate for emotional experience, and low for social experience. The implications of this study suggest that interactive games have the potential to serve as effective educational tools for special needs students, particularly in enhancing student engagement and competency, underlining the significance of learning experiences in alignment with national inclusive education objectives.